0326 Identification of Objective and Subjective Markers of Sleep Health. (27th April 2018) - Allen, S; Elder, G; Sharman, R; Gotts, Z M; Ellis, J G
Abstract: Introduction: While the concept of 'sleep health' has only recently been defined, how it relates to both subjective and objective sleep parameters has yet to be determined. The current study aimed to identify potential sleep (subjective and objective) markers of sleep health in a sample of healthy adults. Methods: A cross-sectional study with both a questionnaire-based and an in-lab component was conducted with eighty-three 'normal sleepers' (aged 18–65). All participants reported no history of insomnia, any other sleep disorders or chronic physical or psychiatric illnesses. A selection of questions from various psychometric scales were used to determine sleep health status. Measures of psychological distress, perceived stress, stressful life events, sleep beliefs, sleep preoccupation and insomnia vulnerability were also administered. Subjective sleep continuity was assessed by two-week sleep diary. Objective measures comprised 14 days of actigraphy and two-nights of in-lab polysomnography (PSG). Results: Significant correlations were found between sleep health status and subjective Sleep Efficiency (diary) and Sleep Latency (from both diary and actigraphy). Independent samples t-tests between high and low sleep health groups reflected this. No relationships between sleep health and PSG parameters were not observed. Regression analyses indicated SOL (diary) and SOL (actigraphy) were significant predictors of sleep health, explaining 24.9% of the variance in scores. Conclusion: Sleep health is likely to be a largely subjective and multidimensional concept, which may be predicted by perceived sleep latency and sleep efficiency. However, it is suggested that PSG sleep parameters cannot reliably infer sleep health status in normal sleepers. Future research is warranted to determine the dimensionality of the concept, and the physical and psychological correlates of sleep health in larger samples. Support (If Any): This study was funded by The Sleep Council.